Use of transoral endoscopy for pharyngeal examination: Cross‐sectional analysis. Issue 3 (28th November 2013) - Tsuji, Kunihiro; Doyama, Hisashi; Takeda, Yasuhito; Takemura, Kenichi; Yoshida, Naohiro; Kito, Yosuke; Asahina, Yoshiro; Ito, Renma; Nakanishi, Hiroyoshi; Hayashi, Tomoyuki; Inagaki, Satoko; Tominaga, Kei; et al.
<x xml:space="preserve">Abstract</x> Background and Aim Transoral endoscopy with narrow band imaging (NBI) is useful for identifying early‐stage head and neck cancer. However, the screening capability of transoral upper gastrointestinal endoscopy has not yet been systematically evaluated. We evaluated the usefulness of transoral upper gastrointestinal endoscopy for pharyngeal examination. Methods This cross‐sectional study evaluated 480 patients. All endoscopic pharyngeal examinations with NBI were carried out in accordance with prescribed procedures, consisting of 10 images each and all images were assessed by a blinded reviewer. We examined the association between the diagnostic usefulness of pharyngeal examination and other factors. Results Median subject age was 64 years (range 22–90 years), and 64% were male. Almost all patients (98%) had an Eastern Cooperative Oncology Group Performance Status of 0 or 1.Butylscopolamine bromide was given to 382 patients (80%), and a sedative was given to 460 (96%) patients. Median observation time was 74 s (range, 16–362 s), resulting in a mean of 9.0 usable images per patient. However, photographs of the right and left pyriform sinuses were consistently poor. Ordered logistic regression analysis showed that quality images were positively correlated with increased patient age. Conclusions Transoral endoscopic examination was possible in most patients for screening of the head and neck. However, results were poor in the pyriform sinuses, indicating that additional improvements of examination methods and instruments are needed to enhance screening accuracy.